Multicomorbidity in Psoriasis Vulgaris: A Retrospective Analysis - Fettahlioglu Karaman B; Salkin Cinki IA; Aksungur VL (Dove Medical Press, 2024)
Bilge Fettahlioglu Karaman,* Irem Ayse Salkin Cinki,* Varol Lutfu Aksungur* Cukurova University, Medical School, Department of Dermatology, Adana, Turkey*These authors contributed equally to this workCorrespondence: Bilge Fettahlioglu Karaman, Cukurova University, Medical School, Department of Dermatology, Saricam, Adana, 01330, Turkey, Tel +90 533 5622626, Fax +90 322 3387144, Email bilgef@gmail.comBackground: The frequencies of comorbidities in patients with psoriasis have been compared to that in the general population in many studies. Moreover, several studies have investigated the risk factors influencing the number of comorbidities in patients with psoriasis. However, a few studies have examined clusters of patients with psoriasis according to their comorbidities. In this study, we aimed to explore the multicomorbidities of psoriasis vulgaris in terms of risk factors and clusters.Methods: All diagnoses of 452 patients with psoriasis vulgaris were extracted from electronic medical records of a tertiary hospital. Binary association coefficients were calculated for all pairs of comorbidities. Subsequently, a hierarchical cluster analysis was performed.Results: Among the patients, 30.5% had no comorbidities, 28.8% had a single comorbidity, and 40.7% had multiple comorbidities. The number of comorbidities was positively associated with age and follow-up duration but not with sex. The most striking cluster of comorbidities was composed of diabetes, hepatosteatosis, hyperlipidemia, hypertension, cancer, and cardiovascular disease.Conclusion: This cluster could be explained by cardiometabolic multimorbidity. Exploring such clusters may provide a more forward-looking perspective for the management of psoriasis patients.Keywords: psoriasis vulgaris, comorbidities, cluster analysis, retrospective